Pengaruh Motivasi, Kompetensi Dan Komitmen Terhadap Kinerja Dosen Pada Perguruan Tinggi Swasta Di Lingkungan Kopertis Wilayah II Palembang (Survey pada Perguruan Tinggi Swasta di Kopertis Wilayah II Palembang) - Nur'aeni Nur'aeni (Indonesian Journal of Economics and Business, 2011)
Motivation, competence and commitment often as mayor to influence lecturers private higher education performance. The objectives of this research are : (1) to find outcome analysis of motivation, (2) to find outcome analysis of  competence, (3) to find outcome analysis of commitment, (4) to find out come analysis of lecturers performanc, (5) to find out come analysis motivation, competence and commitment influences to lecturers performance. The research method are use descriptive and explanatory survey with questionnaires as an instrument of the primary data collection. Sample size is 300 lecturers that be taken sample quota which information centre the head of department in 41  universities regional II Palembang environment, data analysis is using the structural equation model (SEM). Analysis results showed that ; level of motivation in the higher category, level of competence in the competent category, ; level of commitment in the higher category, level of lecturer performance in the higher category. Motivation, competence and commitment have a meaningful relationship to the lecturers performance.